From the mixed-up files of Mrs. Basil E. Frankweiler - Konigsburg, E. L. (New York : Dell, 1973)
Having run away with her younger brother to live in the Metropolitan Museum of Art, twelve-year-old Claudia strives to keep things in order in their new home and to become a changed person and a heroine to herself.
Keywords: Runaways -- Juvenile fiction; Siblings -- Juvenile fiction